2018
DOI: 10.15835/nsb10310273
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Organic Mulch Materials on Soil Surface Evaporation

Abstract: The effects of organic mulching material on soil surface evaporation were studied in Abia State. The objective of the study was to compare impact of mulch materials on saturated hydraulic conductivity and surface evaporation. The organic mulch materials were composted and non-composted Calapogonuim, Chromolena and Panicum spp. The design was randomized complete block design (RCBD). Data generated were statistically analysed. Analysis of variance was used to compare the influence of mulch materials on the measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
(12 reference statements)
0
1
0
Order By: Relevance
“…The lower volumetric water content of soils under excavation site may be due to their higher capillary rise (as a result of the high clay content) which may have stimulated the evaporation of soil moisture (Nugraha et al, 2016). Uzoma and Onwuka (2018), reported that continuous evaporation of soil moisture reduced the volumetric moisture content of soil.…”
Section: Soil Temperaturementioning
confidence: 99%
“…The lower volumetric water content of soils under excavation site may be due to their higher capillary rise (as a result of the high clay content) which may have stimulated the evaporation of soil moisture (Nugraha et al, 2016). Uzoma and Onwuka (2018), reported that continuous evaporation of soil moisture reduced the volumetric moisture content of soil.…”
Section: Soil Temperaturementioning
confidence: 99%